2013
DOI: 10.1097/dcr.0b013e3182758c2b
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Use of Sphincter-Preserving Surgery in Patients With Rectal Cancer

Abstract: These data suggest that the receipt of a permanent colostomy by many patients with rectal cancer may be inappropriate, and there is potential to increase the use of sphincter-preserving surgery in patients with rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 31 publications
0
26
2
1
Order By: Relevance
“…For example, previous research has suggested that female gender, lower stages and lower BMI, are associated with SPS. 4,5 In the present analysis, these associations are eliminated after adjusting for tumor location and the incorporation of a unique hospital identifier in the multivariable model. One can conclude that even among strictly defined eligibility criteria, some institutions have different practice patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, previous research has suggested that female gender, lower stages and lower BMI, are associated with SPS. 4,5 In the present analysis, these associations are eliminated after adjusting for tumor location and the incorporation of a unique hospital identifier in the multivariable model. One can conclude that even among strictly defined eligibility criteria, some institutions have different practice patterns.…”
Section: Discussionmentioning
confidence: 99%
“…1 Modern techniques and stapling technology frequently permit sphincter preserving surgery (SPS) and the avoidance of a permanent stoma, even for low-lying tumors. 25 Accordingly, SPS-rates have been proposed as a quality measure for rectal cancer surgery and multiple reports have shown wide variations in its utilization. 6,7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Population-based rates of SPS in Europe and Australia vary between 75-84% while rates in the US are anywhere between 48-77%. 4,5 Moreover, previous studies using national registry data and hospital discharge data have shown that SPS rates vary based on patient demographics, education, geography and surgeon volume. 4,[8][9][10][11][12] However, these data lack critical clinical details, such as tumor location or sphincter involvement, which are necessary to determine if patients are candidates for SPS.…”
Section: Introductionmentioning
confidence: 99%
“…1 Modern techniques and stapling technology frequently permit sphincter preserving surgery (SPS) and the avoidance of a permanent stoma, even for low-lying tumors. [2][3][4][5] Accordingly, SPSrates have been proposed as a quality measure for rectal cancer surgery and multiple reports have shown wide variations in its utilization. 6,7 Population-based rates of SPS in Europe and Australia vary between 75-84% while rates in the US are anywhere between 48-77%.…”
Section: Introductionmentioning
confidence: 99%